2013
DOI: 10.7482/0003-9438-56-015
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation in cows synchronized with two different progesterone+oestradiol protocols

Abstract: Abstract. A total of 26 Brown Swiss cows were used to compare the synchronization and superovulatory response of follicle stimulating hormone treated cows that were synchronized with progesterone+oestradiol valerate or benzoate. Control cows (n = 8) were superstimulated with follicle stimulating hormone using twice daily injections with decreasing doses from day 10–13 after determined reference oestrus. Cows in treatment groups were received either ear implant (n = 9) containing norgestomet+oestradiol valerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
1
Order By: Relevance
“…The average of corpus luteum in Pesisir cattle after the injection of 16 ml dosage of FSH was 2.97 ± 1.69, whicj was lower than that observed by Nilchuen et al (2012) Bülbül et al(2013) got the CL average 8.4±1.6 on twice a day injection of 400 mg FSH also 150 µg D-cloprostenol together with the fifth FSH induction to Brown Swiss cattle race. Ali et al (2012) reported that in local cattle of Bangladesh the injection of 320 mg FSH gave the best respond on the corpus luteum quantity 13.60±0.51 meanwhile the lowest average is 8.60±0.60 from the quantity of corpus luteum on 200 mg FSH.…”
Section: Resultscontrasting
confidence: 58%
“…The average of corpus luteum in Pesisir cattle after the injection of 16 ml dosage of FSH was 2.97 ± 1.69, whicj was lower than that observed by Nilchuen et al (2012) Bülbül et al(2013) got the CL average 8.4±1.6 on twice a day injection of 400 mg FSH also 150 µg D-cloprostenol together with the fifth FSH induction to Brown Swiss cattle race. Ali et al (2012) reported that in local cattle of Bangladesh the injection of 320 mg FSH gave the best respond on the corpus luteum quantity 13.60±0.51 meanwhile the lowest average is 8.60±0.60 from the quantity of corpus luteum on 200 mg FSH.…”
Section: Resultscontrasting
confidence: 58%